2006
DOI: 10.1111/j.1475-1313.2006.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with the carotenoids lutein or zeaxanthin improves human visual performance

Abstract: The results suggest that supplementation with L or Z increases MPOD at the fovea and at 2.5 degrees , and that supplementation can improve CATs at high mesopic levels and hence visual performance at low illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 24 publications
4
82
1
1
Order By: Relevance
“…Many cross-sectional studies have shown a positive association between MP and measures of visual performance, including visual acuity, contrast sensitivity (CS), photostress recovery and glare disability (among others). [31][32][33][34][35] It has also been shown that supplementation with the macular carotenoids improves parameters of visual function in patients afflicted with the early form of this condition. [36][37][38] However, no study has yet investigated the impact of a formulation containing MZ on visual function in subjects with early AMD, or on the natural course of this condition.…”
mentioning
confidence: 99%
“…Many cross-sectional studies have shown a positive association between MP and measures of visual performance, including visual acuity, contrast sensitivity (CS), photostress recovery and glare disability (among others). [31][32][33][34][35] It has also been shown that supplementation with the macular carotenoids improves parameters of visual function in patients afflicted with the early form of this condition. [36][37][38] However, no study has yet investigated the impact of a formulation containing MZ on visual function in subjects with early AMD, or on the natural course of this condition.…”
mentioning
confidence: 99%
“…The extent of macular pigmentation has recently been found to be related to the width of the foveal cup, as assessed by optical coherence tomography 3 . Since these pigments are located in the fibers of Henle at the foveola and in the inner nuclear layer beyond the foveola 4 , they act as a prereceptoral filter and are believed to contribute a variety of potentially beneficial properties for vision, including reduction of the effects of chromatic aberration 5 (though not supported by Engles et al 6 ,), improvement of spatial vision and contrast enhancement 7 , increased photopic increment sensitivity 8 , reduced glare sensitivity in some studies 9,10 but not others 11 , and increased critical flicker frequency 12 .…”
mentioning
confidence: 99%
“…MP is a blue light filter (Snodderly et al, 1984b) and a powerful antioxidant, (Khachik et al, 1997) and is therefore believed to protect against age-related macular degeneration (AMD), which is now the most common cause of blind registration in the western world (Klaver et al, 1998). In addition, MP's putative ability to enhance visual performance and comfort is also of interest (Bartlett and Eperjesi, 2008;Engles et al, 2007;Hammond and Wooten, 2005;Kvansakul et al, 2006;Loughman et al, 2010;Nolan et al, 2011;Rodriguez-Carmona et al, 2006;Hammond, 2007, 2008;Stringham et al, 2004;Wooten and Hammond, 2002).…”
Section: Introductionmentioning
confidence: 99%